Comparison of eleven commercially available rapid tests for detection of Bacillus anthracis, Francisella tularensis and Yersinia pestis. (8th February 2015) - Zasada, A.A.; Formińska, K.; Zacharczuk, K.; Jacob, D.; Grunow, R.
Abstract Yersinia pestis, Bacillus anthracis and Francisella tularensis cause serious zoonotic diseases and have the potential to cause high morbidity and mortality in humans. In case of natural outbreaks and deliberate or accidental release of these pathogens rapid detection of the bacteria is crucial for limitation of negative effects of the release. In the present study, we evaluated 11 commercially available rapid test kits for the detection of Y. pestis, B. anthracis and F. tularensis in terms of sensitivity, specificity and simplicity of the procedure. The results revealed that rapid and easy‐to‐perform lateral flow assays for detection of highly pathogenic bacteria have very limited sensitivity. In contrast, the immunofiltration assays showed high sensitivity but limited specificity and required a too complicated procedure to be applied in the field by nonlaboratory workers (e.g. First Responders like fire, police and emergency medical personnel). Each sample ‐ whether tested negative or positive by the rapid tests ‐ should be retested in a reference laboratory using validated methods. Significance and Impact of the Study Rapid detection of highly pathogenic bacteria causing anthrax, plague and tularemia is crucial for the limitation of negative effects of a potential release (natural, accidental or deliberate). In the study, commercially available rapid tests for detection of Bacillus anthracis, Yersinia pestis and Francisella tularensis were investigated in terms of sensitivity, specificity and ease‐to‐perform. The study showed problems which could be faced during testing and results interpretation. Conclusions from this study should be helpful not only in selection of the most appropriate test for particular group of First Responders but also in undertaking decisions in situation of a contamination suspicion which have high social and economical impacts.